Multigrid solver for the reference interaction site model of molecular liquids theory - Sergiievskyi, Volodymyr P.; Hackbusch, Wolfgang; Fedorov, Maxim V. (Journal of computational chemistry, 2011)
In this article, we propose a new multigrid‐based algorithm for solving integral equations of the reference interactions site model (RISM). We also investigate the relationship between the parameters of the algorithm and the numerical accuracy of the hydration free energy calculations by RISM. For this purpose, we analyzed the performance of the method for several numerical tests with polar and nonpolar compounds. The results of this analysis provide some guidelines for choosing an optimal set of parameters to minimize computational expenses. We compared the performance of the proposed multigrid‐based method with the one‐grid Picard iteration and nested Picard iteration methods. We show that the proposed method is over 30 times faster than the one‐grid iteration method, and in the high accuracy regime, it is almost seven times faster than the nested Picard iteration method. © 2011 Wiley Periodicals, Inc. J Comput Chem, 2011